Synthesis of fatty acid methyl ester from rice bran oil - Gunasekeran, Nithya; Koria, Litty (Journal of Ecobiotechnology, 2012)
Increase in urbanization, standard of living of people and expanding population are the key factors which contribute to the growth in energy demand. India ranks sixth in the world in terms of energy demand. Indiaâ€™s demand for diesel fuel is increasing rapidly and much of the increase has to be met with expensive oil import. The known world wide reserves of petroleum are predicted to last for about 40 years, hence future availability of petroleum is uncertain. Alternative fuels have to be considered in order to undertake energy security and import substitution for diesel crude imports by 5% in 2015 and 10% in 2020. In this circumstances non-edible oil source play a vital role to meet the diesel requirement. In the present study, biodiesel has been prepared from Rice Bran oil by transesterification method.Â 